2017
DOI: 10.1080/09513590.2017.1404238
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunological parallels in pregnancy loss

Abstract: Peculiar characteristics of cytotoxic endometrial cells' response depending on the clinical aspects (frequency, gestational age, form of miscarriage, hysteroscopic pattern) have been studied. Patients with pregnancy loss in their past medical history demonstrate a decreased level of CD8 þ lymphocytes, and the decrease is exacerbated as the incidence of miscarriages increases and in the presence of endometrial hypoplasia. The content of CD16 þ lymphocytes increases in comparison with the control group, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…A higher endometrial CD4/CD8 ratio, elevated CD4 levels and lower CD8 have all been reported in women with implantation failure when compared to controls [38]. Reduced CD8 levels have also been reported in recurrent pregnancy loss [39]. Examining concentrations in this study has shown that CD4 and CD8 counts are significantly lower in implantation failure perhaps supporting a role, either directly or indirectly, for these cells in this complex process.…”
Section: Discussionsupporting
confidence: 68%
“…A higher endometrial CD4/CD8 ratio, elevated CD4 levels and lower CD8 have all been reported in women with implantation failure when compared to controls [38]. Reduced CD8 levels have also been reported in recurrent pregnancy loss [39]. Examining concentrations in this study has shown that CD4 and CD8 counts are significantly lower in implantation failure perhaps supporting a role, either directly or indirectly, for these cells in this complex process.…”
Section: Discussionsupporting
confidence: 68%
“…[31] In Kazakhstan, the rate of preterm birth remains at the level of 6.4% [32][33][34] according to official data and reports of domestic authors, and according to the WHO it is 8.8 cases per 100 births. [35] Urinary tract infections, which are also one of the causes of cerebral palsy, also remain at the same level [33,34,36], they are also often the cause of premature birth, which in combination can give an increased risk of developing cerebral palsy in the fetus / child [26][27][28], especially noted pyelonephritis [29], which in our work reliably showed a connection in the development of cerebral palsy.…”
Section: Discussionsupporting
confidence: 56%
“…It should be borne in mind that numerous medications can affect spermatogenesis, which makes their use preferable from the perspective of male infertility treatment. At the same time, endocrine disorders rarely directly lead to infertility [17,[29][30][31] .…”
Section: Discussionmentioning
confidence: 99%